Maintaining Riau Malay Language Features through Phonological Innovations in Kampar District - Juli Yani; Sisi Rosida; Rahimi Rahimi; Eko Firman Susilo (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
The maintenance that occurs in language arises because there are causes that are very closely related to changes in language observed in certain elements found in dialect varieties, regional boundaries, number of speakers, place of residence, identity and cultural pride, and good economic conditions. This study aimed to determine (1) lexical forms of phonology and (2) the geographic distribution of phonological forms that experience variations in Riau Malay in Kampar Regency. This study uses a descriptive method with listening techniques, interviews, and recordings. The results of this study are based on its embodiment; the determination of phonetic innovation is based on the discovery of a variant that indicates a phonotactic change from the original variant at the Riau Malay observation point in Kampar Regency. The study results noted that there were 24 glosses with 67 variants indicating this type of innovation.